Contributions of Education for Sustainable Development (ESD) to Quality Education - Dr. Kaushlendra Dixit (JOURNAL OF INDUSTRIAL RELATIONSHIP CORPORATE GOVERNANCE AND MANAGEMENT EXPLORER, 2023)
In today’s interconnected world, information is easily acquired. Facts that professionals once collected as a result of years of study are now readily available on the Internet. Today’s education requires knowing what to do with information, that is, how to analyze it; make sense of its abundance and complexity; cooperate with others to synthesize information; and communicate the results. Consequently, quality education is no longer based primarily on fact acquisition. As education based on fact acquisition becomes increasingly outdated, policymakers debate the basis for transforming their education systems. Yet, these transformations require more than a vision of what is possible: they require evidence that will justify such. Evidence-based decision making is both encouraged and of growing importance in the formal education community. The goal of this study is to provide evidence that ESD (Education for Sustainable Development) contributes in many ways to a quality education. Keywords: Education, Sustainable Development, information